Carbon aerogel loaded iron carbon nanospheres as well as preparation method and application thereof
By loading iron nanocarbon balls on the carbon aerogel, using the pseudocapacitance characteristics of Fe3O4 and the high specific surface area of the carbon aerogel, the problems of low voltage window, short discharge time and poor cycle stability of the zinc ion hybrid supercapacitor are solved, and high energy density, long discharge time and good cycle stability are achieved.
Patent Information
- Application Number
- CN202510019137.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
The existing zinc ion hybrid supercapacitors have problems such as low voltage window, short discharge time, low energy density and power density, and poor cycle stability.
By loading iron nanocarbon spheres on carbon aerogels, the structure of carbon aerogels is constructed, and the electrochemical performance and cyclic stability are improved by using the pseudocapacitance characteristics of Fe3O4 and the high specific surface area of carbon aerogels.
The energy density and power density of the capacitor are significantly improved, the discharge time is extended, the cycle stability is improved, and the capacity retention rate reaches 231%.
Smart Images

Figure CN119811904A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of supercapacitors, and in particular to carbon aerogel-loaded iron nano-carbon spheres and a preparation method and application thereof. Background Art
[0002] As a new type of energy storage device, zinc-ion hybrid supercapacitors combine the advantages of zinc-ion batteries and supercapacitors and have excellent energy density and power density. However, the electrochemical decomposition voltage of water limits the operating voltage of the battery, thereby affecting the energy density and output, severely limiting the performance and life of zinc-ion hybrid supercapacitors and hindering their large-scale application.
[0003] In order to improve the energy density and cycle life of the capacitor, a carbon material with high conductivity, good chemical stability and large specific surface area can be used as the positive electrode material of the zinc ion hybrid supercapacitor. For example, the existing document 1 (Coffee waste-derived porous carbon based flexible supercapacitors, Chemical Physics Letters, 2022, 809: 140173. DOI: 10.1016 / j.cplett.2022.140173) uses coffee grounds derived carbon as an electrode material. Under the condition of a current density of 5A / g, the number of cycles is 5000 times, and the capacity retention rate is 90.5%. However, this technology has the problems of low voltage window and short discharge time. The reason is that the biomass carbon material used in this technical solution has the structural characteristics of uneven structure and more surface defects, which leads to its poor electrochemical performance.
[0004] In order to solve the problem of low voltage window, it can be achieved by coating transition metal oxides or carbon materials on the surface of the material. For example, existing document 2 (N-doped carbon-coated TiN exhibiting excellent electrochemical performance for supercapacitors, Electrochimica Acta, 2017, 257: 56-63. DOI: 10.1016 / j.electacta.2017.10.066) coats a layer of nitrogen-doped carbon on the outside of TiN nanoparticles. This structure can improve the oxidation resistance of TiN. After forming a double electrode, the voltage window can be increased to 1.6V, and, under the condition of a current density of 1A / g, the number of cycles is 5000 times, and the capacity retention rate is 92%. However, the discharge time of this technology is only 320s at a current density of 0.2A / g, that is, there is a problem of short discharge time, which directly leads to low energy density and power density. The reason is that although the nitrogen-doped carbon layer can increase the voltage window of the electrode material, the nitrogen-doped carbon layer has uneven electrochemical activity, which leads to uneven charge distribution, which directly leads to an increase in interface impedance and a decrease in conductivity.
[0005] In order to improve the energy density and power density, it can be achieved by loading oxygen-rich carbon materials on the surface of the material. For example, the existing document 3 (Core-shell Fe3O4@carbon aerogels assembled aqueous zinc ion hybrid capacitor with ultra-wide voltage window, Journal of Energy Storage, 2023, 72: 108798. DOI: 10.1016 / j.est.2023.108798) loads a layer of carbon aerogel outside the Fe3O4 ball. The carbon aerogel and the Fe3O4 ball can contribute double-layer capacitance and pseudocapacitance at the same time under the synergistic effect, thereby improving the energy density and power density. At a current density of 0.5A / g, the discharge time is increased to 340s, and at a power density of 210W / kg, the energy density is 284.7Wh / kg. However, this technology has the problem of poor cycle stability. At a current density of 5A / g, the number of cycles is 10,000 times, and the capacity retention rate is 75%. The reason is that the carbon aerogel spherical particles loaded on the surface of the Fe3O4 balls have a particle size of 30-50nm. During the long cycle process, there is a phenomenon of falling off from the surface of the Fe3O4 balls, resulting in poor cycle stability.
[0006] Therefore, based on the above-mentioned prior art solutions, it can be known that the prior art achieves the technical effect of expanding the voltage window by coating the carbon material on the surface of the material. However, this type of technical solution has the problems of short discharge time, low energy density and power density. The current common solution is to use transition metal oxides as a coating layer, which can be evenly distributed on the surface of the material to expand the voltage window. Although this method can improve the power density and energy density, it will cause new technical problems-some transition metal oxides will agglomerate in the solution, resulting in reduced cycle stability of the electrode material. The solution is to improve the method of fixing the load after coating the surface of the material. Although this method can improve the short-term cycle stability, the active substance still has the problem of falling off during long-term cycles, resulting in the cycle stability improvement effect not meeting expectations. Summary of the invention
[0007] The purpose of the present invention is to provide a carbon aerogel loaded iron nanocarbon sphere and its preparation method and application. In view of the technical problems existing in the prior art, the following methods are adopted to solve the above problems:
[0008] 1. Porous carbon is obtained by calcining ZIF-8 at high temperature, and used as a carrier, mixed with ferric chloride in ethylene glycol solution, and then anhydrous sodium citrate and anhydrous sodium acetate are added for stirring, and a hydrothermal reaction is performed to form iron nanocarbon balls to improve the electrochemical performance;
[0009] 2. Carry out hydrothermal reaction between carbon aerogel and iron nano-carbon spheres to construct a carbon aerogel-loaded iron nano-carbon sphere structure to improve the electrochemical performance and cycle stability.
[0010] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0011] A carbon aerogel loaded with iron nano-carbon spheres, using chitosan and glacial acetic acid as raw materials, freeze-drying and then calcining at high temperature to obtain carbon aerogel; using zinc nitrate hexahydrate, 2-methylimidazole, methanol, and ethanol as raw materials, standing at room temperature and then calcining at high temperature to obtain porous carbon; using ferric chloride and porous carbon as raw materials, hydrothermal reaction to obtain iron nano-carbon spheres;
[0012] The carbon aerogel loaded with iron nano-carbon spheres consists of a sheet structure and a nano-spherical structure, wherein the nano-spherical structure is loaded on the surface of the sheet structure;
[0013] The specific surface area of the carbon aerogel is 950-1000m 2 / g, contains a large number of micropores and mesopores, and the specific surface area of the carbon aerogel loaded with iron nanocarbon spheres is 750-800m 2 / g, including micropores and mesopores.
[0014] A method for preparing carbon aerogel-loaded iron nanocarbon spheres comprises the following steps:
[0015] Step 1, preparation of chitosan-based carbon aerogel, first, chitosan and glacial acetic acid meet a certain mass ratio, chitosan is dissolved in an aqueous solution to obtain a chitosan solution, then the chitosan solution is stirred under certain conditions, then glacial acetic acid is added to the chitosan solution, and stirring is continued under certain conditions, freeze-dried after stirring, and finally, the obtained product is calcined under certain conditions to achieve carbonization, so as to obtain chitosan-based carbon aerogel, referred to as CA;
[0016] In the step 1, the mass ratio of chitosan to glacial acetic acid is 5:3;
[0017] In step 1, the freeze-drying conditions are at -50°C for 65-75h;
[0018] In step 1, the calcination conditions are: the calcination temperature is 800° C. and the calcination time is 1-2 h;
[0019] Step 2, preparation of Fe3O4-coated porous carbon nanospheres, first prepare a porous carbon material based on ZIF-8, and then coat Fe3O4 on the porous carbon material to obtain Fe3O4-coated porous carbon nanospheres, i.e., iron nanocarbon spheres, referred to as Fe / C-8; wherein,
[0020] The preparation of the porous carbon material based on ZIF-8 is step 2.1, specifically,
[0021] Preparation of porous carbon: first, 2-methylimidazole and zinc nitrate satisfy a certain mass ratio, 2-methylimidazole is dissolved in a mixed solvent to obtain an imidazole solution, and zinc nitrate solid is dissolved in the mixed solvent to obtain a zinc nitrate solution, then, at room temperature and under ultrasonic conditions, the imidazole solution is slowly poured into the zinc nitrate solution to obtain a mixed solution, then, the mixed solution is stirred under certain conditions, after stirring, ZIF-8 is obtained by standing, centrifugal washing and vacuum drying, and finally, ZIF-8 is calcined under certain conditions to achieve carbonization, and the calcined product is ground to obtain porous carbon, referred to as C-8;
[0022] In the step 2.1, the mass ratio of 2-methylimidazole to zinc nitrate is (1-2):1; the mixed solvent is a mixed solution of methanol and ethanol, and the volume ratio of methanol to ethanol is 1:1;
[0023] In the step 2.1, the stirring conditions of the mixed solution are: the stirring speed is 500-1500 rpm, and the stirring time is 5-15 min;
[0024] In step 2.1, the centrifugal washing conditions are: the centrifugal speed is 8000 rpm, the centrifugal time is 5 min, the washing solution is ethanol, and the number of centrifugal washings is 4-6 times;
[0025] In step 2.1, the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 6-10 h.
[0026] In step 2.1, the calcination conditions are: the calcination temperature is 950° C. and the calcination time is 1-2 h;
[0027] The preparation of Fe3O4-coated nanoporous carbon spheres is step 2.2, specifically,
[0028] Preparation of Fe3O4-coated nanoporous carbon spheres: first, porous carbon, ferric chloride, anhydrous sodium citrate and anhydrous sodium acetate satisfy a certain mass ratio, the porous carbon, ferric chloride and anhydrous sodium citrate obtained in step 2.1 are placed in an ethylene glycol solution to obtain a solution A, then the solution A is stirred under certain conditions to obtain a solution B, then anhydrous sodium acetate is placed in the solution B to obtain a solution C, then the solution C is continued to be stirred under certain conditions to obtain a reaction solution, finally, the reaction solution is subjected to a hydrothermal reaction under certain conditions, the product obtained by the hydrothermal reaction is washed and dried, and Fe3O4-coated nanoporous carbon spheres, i.e., iron nanocarbon spheres, referred to as Fe / C-8;
[0029] In the step 2.2, the mass ratio of porous carbon, ferric chloride, anhydrous sodium citrate and anhydrous sodium acetate is 1:10:(3-4):20;
[0030] In step 2.2, the hydrothermal conditions are 200° C. for 15-17 h;
[0031] In step 2.2, the drying conditions are as follows: the drying temperature is 60-80°C and the drying time is 10-14h;
[0032] Step 3, preparation of carbon aerogel-supported iron nano-carbon spheres, first, with iron nano-carbon spheres, anhydrous sodium citrate and carbon aerogel satisfying a certain mass ratio, the iron nano-carbon spheres obtained in step 2.2, the carbon aerogel obtained in step 1 and anhydrous sodium citrate are placed in an ethylene glycol solution to obtain a D solution, then, the D solution is stirred under certain conditions to obtain an E solution, then, the E solution is subjected to a hydrothermal reaction under certain conditions, and the product obtained by the hydrothermal reaction is washed and dried to obtain carbon aerogel-supported iron nano-carbon spheres, referred to as CA / (Fe / C-8);
[0033] In the step 3, the mass ratio of iron nanocarbon spheres, anhydrous sodium citrate and carbon aerogel is 1:8:10;
[0034] In step 3, the hydrothermal condition is 200° C. for 15-17 h;
[0035] In step 3, the drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 10-14 hours.
[0036] When carbon aerogel loaded iron nanocarbon spheres are used as supercapacitor electrode materials, in three electrodes, when the current density is 0.5A / g, the charge and discharge voltage range is -1-0.5V, and the discharge time is 500-550s;
[0037] In the dual electrode, when the current density is 0.5A / g, the charge and discharge voltage range is 0-2.1V, and the discharge time is 2500-3000s, that is, under the condition of power density of 520-530W / kg, the energy density is 400-410Wh / kg;
[0038] At a current density of 5 A / g, the cycle number was 10,000 times and the capacity retention rate was 231%.
[0039] The beneficial technical effects obtained by the present invention are known through testing:
[0040] XRD and EDS tests proved that step 2.1 successfully removed the Zn element and realized the carbonization of ZIF-8 to obtain C-8; step 2.2 coated Fe3O4 on the porous carbon surface, that is, Fe / C-8 was successfully prepared; step 3 loaded iron nanocarbon spheres on the carbon aerogel surface, that is, CA / (Fe / C-8)-10 was successfully prepared, and EDS supplemented the proof that CA / (Fe / C-8)-10 is composed of three elements: Fe, C, and O, specifically including carbon and Fe3O4.
[0041] SEM tests show that the CA obtained in step 1 has a lamellar structure with a smooth surface; the Fe / C-8 obtained in step 2.2 has a uniform spherical structure; the CA / (Fe / C-8)-10 obtained in step 3 is composed of a lamellar structure and a nano-spherical structure, wherein the nano-spherical structure is loaded on the surface of the lamellar structure.
[0042] The BET test showed that the specific surface area of the CA obtained in step 1 was 950-1000m 2 / g, containing a large number of micropores and mesopores; the specific surface area of CA / (Fe / C-8)-10 obtained in step 3 is 750-800m 2 / g, that is, the iron nano-carbon balls cover the micropores and mesopores on the surface of the carbon aerogel, which proves that the iron nano-carbon balls are successfully loaded on the surface of the carbon aerogel.
[0043] CV tests have shown that CA / (Fe / C-8)-10 exhibits both double-layer capacitance and pseudocapacitance behavior.
[0044] GCD testing has proved that Fe3O4 provides additional pseudocapacitance and expands the voltage window. After the carbon aerogel is loaded with iron nano-carbon spheres, it provides more active sites, significantly improves the energy density by 362%, and ensures that the iron nano-carbon spheres are not prone to agglomeration in the solution. It has good cycle stability and a capacity retention rate of 231%.
[0045] In the three-electrode CA / (Fe / C-8)-10, when the current density is 0.5A / g, the charge and discharge voltage range is -1-0.5V, and the discharge time is 500-550s. In the two-electrode, when the current density is 0.5A / g, the charge and discharge voltage range is 0-2.1V, and the discharge time is 2500-3000s. That is, under the condition of power density of 520-530W / kg, the energy density is 400-410Wh / kg. Under the condition of current density of 5A / g, the number of cycles is 10,000 times, and the capacity retention rate is 231%.
[0046] Therefore, the present invention has the following advantages over the prior art:
[0047] 1. Transition metal oxide Fe3O4 has the characteristics of high theoretical specific capacity, low cost and environmental protection, as well as good compatibility with carbon materials. As a coating layer, it can ensure the double-layer capacitance characteristics of carbon materials, provide additional pseudocapacitance characteristics, expand the voltage window, and improve electrochemical performance;
[0048] 2. Use carbon aerogel to load iron nano-carbon spheres to solve the problem of easy agglomeration of iron nano-carbon spheres in solution. At the same time, carbon aerogel can also provide more active sites for electrode materials, improving electrochemical performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 XRD diagrams of ZIF-8, C-8, CA in Example 1 and ZnO / C in Comparative Example 1;
[0050] Figure 2 The SEM images of CA, Fe / C-8, and CA / (Fe / C-8)-10 in Example 1 are shown;
[0051] Figure 3 It is the BET diagram of CA and CA / (Fe / C-8)-10 in Example 1;
[0052] Figure 4 GCD diagrams of Fe / C-8, CA / (Fe / C-8)-10, C-8, CA in Example 1, CA / Fe-10 in Comparative Example 2, and CA / (Fe / C-8)-8 in Comparative Example 3;
[0053] Figure 5 XRD diagrams of Fe / C-8, CA / (Fe / C-8)-10 in Example 1, CA / Fe-10 in Comparative Example 2, and CA / (Fe / C-8)-8 in Comparative Example 3;
[0054] Figure 6 GCD diagrams of Fe / C-8, CA / (Fe / C-8)-10 in Example 1 and CA / (Fe / C-8)-8 in Comparative Example 3;
[0055] Figure 7 is the EDS graph of CA / (Fe / C-8)-10 in Example 1;
[0056] Figure 8 CV diagram of CA / (Fe / C-8)-10 in Example 1;
[0057] Fig. 9 This is the cyclic stability performance diagram of CA / (Fe / C-8)-10 in Example 1. DETAILED DESCRIPTION
[0058] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0059] Example 1
[0060] A method for preparing carbon aerogel-loaded iron nanocarbon spheres comprises the following steps:
[0061] Step 1, preparation of chitosan-based carbon aerogel, first, dissolving 1g of chitosan in 40mL of aqueous solution to obtain a chitosan solution, then stirring the chitosan solution for 1h, then adding 0.6mL of glacial acetic acid to the chitosan solution, continuing to stir for 1h, freeze-drying after stirring, finally, calcining the obtained product at a calcination temperature of 800°C for 2h to achieve carbonization, and obtaining chitosan-based carbon aerogel, referred to as CA;
[0062] In step 1, the freeze-drying conditions are as follows: the freeze-drying temperature is -50°C and the freeze-drying time is 72h;
[0063] In order to prove the composition of CA obtained in step 1, XRD test was performed. The test results are as follows Figure 1 As shown, CA only has the characteristic peaks of carbon.
[0064] In order to verify the microstructure of CA obtained in step 1, SEM test was performed. The test results are shown in Figure 2 As shown, CA has a lamellar structure with a smooth surface.
[0065] In order to further verify the microstructure of CA obtained in step 1, BET test was performed. The test results are shown in Figure 3 As shown, the specific surface area of CA is 980m 2 / g; From the isotherm, we can see that CA contains a large number of micropores and mesopores.
[0066] XRD test, SEM test and BET test proved that CA is carbon aerogel.
[0067] The electrochemical test of the present invention involves a three-electrode system and a two-electrode system.
[0068] In the three-electrode system, the material to be tested is used as the working electrode, the mercury / mercury oxide electrode is used as the reference electrode, the platinum electrode is used as the counter electrode, and the 6M KOH solution is used as the electrolyte. The specific preparation method of the working electrode is as follows: the mass ratio of the material to be tested, acetylene black and polytetrafluoroethylene powder is 8:1:1, 0.008g of the material to be tested, 0.001g of acetylene black, 0.001g of polytetrafluoroethylene powder and an appropriate amount of ethanol are weighed and mixed and ground; after grinding, it is dried under an infrared lamp to obtain a dry sample; finally, the dry sample is placed on a 2cm×4cm nickel foam current collector, the nickel foam is folded in half, and the nickel foam is pressed at a pressure of 5kPa to obtain a supercapacitor electrode, i.e., a working electrode.
[0069] In the two-electrode system, the specific preparation method of the negative electrode is: cut a 2cm×2cm square zinc sheet on the zinc foil, and use sandpaper to grind the oxide on the surface to obtain the negative electrode. The positive electrode is the material to be tested. The preparation method is the same as the working electrode preparation method in the three-electrode system, and 2M ZnSO4 solution is used as the electrolyte.
[0070] In order to demonstrate the electrochemical performance of the CA obtained in step 1, a constant current charge-discharge GCD test was performed. The test results are shown in Figure 4 As shown, when the current density is 0.5A / g, the charge and discharge voltage range is -1-0V, and the discharge time is 331s.
[0071] Step 2, preparation of Fe3O4-coated porous carbon nanospheres, first prepare a porous carbon material based on ZIF-8, and then coat Fe3O4 on the porous carbon material to obtain Fe3O4-coated porous carbon nanospheres, i.e., iron nanocarbon spheres, referred to as Fe / C-8; wherein,
[0072] The preparation of the porous carbon material based on ZIF-8 is step 2.1, specifically,
[0073] Preparation of porous carbon: First, 6.92 g of 2-methylimidazole is dissolved in 480 mL of a mixed solvent to obtain an imidazole solution. At the same time, 6.27 g of zinc nitrate hexahydrate solid is dissolved in 480 mL of a mixed solvent to obtain a zinc nitrate solution. Then, at room temperature and under ultrasonic conditions, the imidazole solution is slowly poured into the zinc nitrate solution to obtain a mixed solution. After that, the mixed solution is stirred at a stirring speed of 1000 rpm for 10 min. After stirring, ZIF-8 is obtained by standing, centrifugal washing and vacuum drying. Finally, ZIF-8 is calcined at a calcination temperature of 950 ° C and a calcination time of 2 h to achieve carbonization. The calcined product is ground to obtain porous carbon, referred to as C-8.
[0074] In the step 2.1, the mixed solvent is a mixed solution consisting of methanol and ethanol, and the volume ratio of methanol to ethanol is 1:1;
[0075] In the step 2.1, the standing condition is that the standing time is 24 hours; the centrifugal washing condition is that the washing liquid is ethanol, the centrifugal speed is 8000 rpm, the centrifugal time is 5 minutes, and the number of centrifugal washing times is 4 times; the vacuum drying condition is that the drying temperature is 60°C and the drying time is 8 hours.
[0076] In order to prove the composition of ZIF-8 and C-8 obtained in step 2.1, XRD test was performed. The test results are shown in Figure 1 As shown,
[0077] The diffraction peaks of ZIF-8 are consistent with the characteristic peaks of standard ZIF-8;
[0078] The diffraction peak of C-8 only has the characteristic peak of carbon, but not the characteristic peak of ZIF-8 or the characteristic peak of Zn element, that is, the original characteristic peak of ZIF-8 disappears, and the Zn element is also removed;
[0079] By comparing the test results of ZIF-8 and C-8, it can be seen that after the calcination and carbonization in step 2.1, ZIF-8 is converted into porous carbon, in which the organic ligand is converted into carbon material and the metal Zn is removed.
[0080] In order to prove the electrochemical performance of C-8 obtained in step 2.1, a constant current charge-discharge GCD test was performed. The test results are shown in Figure 4 As shown, when the current density is 0.5A / g, the charge and discharge voltage range is -1-0V, and the discharge time is 360s.
[0081] The preparation of Fe3O4-coated nanoporous carbon spheres is step 2.2, specifically,
[0082] Preparation of Fe3O4-coated nanoporous carbon spheres: First, 0.06 g of the porous carbon obtained in step 2.1, 0.6 g of ferric chloride and 0.2 g of anhydrous sodium citrate are placed in 20 mL of ethylene glycol solution to obtain solution A, then, solution A is stirred for 1 hour to obtain solution B, then 1.2 g of anhydrous sodium acetate is placed in solution B to obtain solution C, then, solution C is stirred for 1 hour to obtain a reaction solution, finally, the reaction solution is subjected to a hydrothermal reaction at a hydrothermal temperature of 200°C and a hydrothermal time of 16 hours, and the product obtained by the hydrothermal reaction is washed and dried to obtain Fe3O4-coated nanoporous carbon spheres, i.e., iron nanocarbon spheres, referred to as Fe / C-8;
[0083] In step 2.2, the drying conditions are as follows: the drying temperature is 60° C. and the drying time is 12 h.
[0084] In order to prove the composition of Fe / C-8 obtained in step 2.2, XRD test was performed. The test results are as follows Figure 5 As shown, Fe / C-8 has characteristic peaks of Fe3O4 in addition to carbon. The test results show that Fe3O4 is successfully loaded on porous carbon through step 2.2.
[0085] In order to verify the microstructure of Fe / C-8 obtained in step 2.2, SEM test was performed. The test results are shown in Figure 2 As shown, Fe / C-8 has a uniform spherical structure with a particle size of 80-100nm.
[0086] In order to prove the electrochemical performance of Fe / C-8 obtained in step 2.2, GCD test was performed. The test results are shown in Figure 4 As shown in the figure, when the current density is 0.5A / g, the charge and discharge voltage range is -1-0.5V, and the discharge time is 327s. Compared with C-8 obtained in step 2.1, although the Fe3O4 coating slightly reduces the discharge time, the charge and discharge voltage range is significantly increased by 0.5V. The test results show that the voltage window can be significantly expanded by coating Fe3O4 to form a nanosphere structure.
[0087] In order to further quantify the electrochemical performance of Fe / C-8 obtained in step 2.2, electrochemical tests were performed in a two-electrode system. The test results are shown in Figure 6 As shown, when the current density is 0.5A / g and the charge and discharge voltage is in the range of 0-2.1V, the discharge time of the dual electrode is 608s, that is, when the power density is 525W / kg, the energy density is 88.67Wh / kg.
[0088] Step 3, preparation of carbon aerogel-loaded iron nano-carbon spheres, first, place 0.025 g of Fe / C-8 obtained in step 2.2, 0.25 g of CA obtained in step 1 and 0.2 g of anhydrous sodium citrate in 20 mL of ethylene glycol solution to obtain solution D, then stir solution D at a stirring speed of 1000 rpm for 10 min to obtain solution E, then, subject solution E to a hydrothermal reaction at a hydrothermal temperature of 200°C for 16 h, wash and dry the product obtained by the hydrothermal reaction to obtain carbon aerogel-loaded iron nano-carbon spheres, referred to as CA / (Fe / C-8), and the CA / (Fe / C-8) obtained in specific example 1 is named CA / (Fe / C-8)-10.
[0089] In step 3, the drying conditions are as follows: the drying temperature is 60° C. and the drying time is 12 h.
[0090] In order to prove the composition of CA / (Fe / C-8)-10 obtained in step 3, XRD test was performed. The test results are as follows Figure 5 As shown, CA / (Fe / C-8)-10 has characteristic peaks of both carbon and Fe3O4. The test results show that step 3 successfully prepared Fe / C-8 loaded on carbon aerogel.
[0091] In order to verify the element distribution of CA / (Fe / C-8)-10, EDS test was performed. The test results are as follows Figure 7 As shown, CA / (Fe / C-8)-10 is composed of three elements: Fe, C, and O, specifically including carbon and Fe3O4.
[0092] In order to verify the microstructure of CA / (Fe / C-8)-10 obtained in step 3, SEM test was performed. The test results are as follows Figure 2 As shown, CA / (Fe / C-8)-10 is composed of a sheet structure and a nano-spherical structure, wherein the nano-spherical structure is loaded on the surface of the sheet structure. Combining steps 1 and 2 and the test results, it can be seen that the iron nano-carbon spheres obtained in step 2 are successfully loaded on the surface of the carbon aerogel CA obtained in step 1.
[0093] In order to further confirm the microstructure of CA / (Fe / C-8)-10 obtained in step 3, BET test was performed. The test results are as follows Figure 3 As shown, the specific surface area of CA / (Fe / C-8)-10 is 769m 2 / g; From the isotherm, it can be seen that CA / (Fe / C-8)-10 contains micropores and mesopores. Compared with the CA obtained in step 1, it can be seen that after Fe / C-8 is loaded on the surface of CA, the specific surface area decreases. The reason is that Fe / C-8 covers some micropores and mesopores on the surface of CA.
[0094] In order to prove the electrochemical performance of CA / (Fe / C-8)-10, GCD test was carried out. The test results are shown in Figure 4 As shown, when the current density is 0.5A / g, the charge and discharge voltage range is -1-0.5V, and the discharge time is 527s.
[0095] Compared with the CA obtained in step 1, the compounding of CA and Fe / C-8 can significantly increase the charge and discharge time by 61.2%.
[0096] Compared with the Fe / C-8 obtained in step 2, the compounding of CA and Fe / C-8 can significantly increase the charge and discharge time by 59.2%.
[0097] Based on the above results, it can be seen that the electrochemical performance of CA and Fe / C-8 after composite is significantly improved compared with that of single component, which shows that there is a synergistic effect between CA and Fe / C-8.
[0098] In order to verify the electrochemical behavior of CA / (Fe / C-8)-10, CV test was performed. The test results are shown in Figure 8 As shown in the figure, under the condition of scanning rate of 50mV / s, when the voltage window is in the range of -1-0V, the CV curve is rectangular; when the voltage window is 0-0.5V, the CV curve has an obvious redox peak, which corresponds to Fe 3+ and Fe 2+ The test results show that CA / (Fe / C-8)-10 exhibits double-layer capacitance behavior in the -1-0V voltage window range and pseudocapacitance behavior in the 0-0.5V voltage window range, which proves that Fe3O4 provides additional pseudocapacitance in CA / (Fe / C-8)-10.
[0099] In order to further quantify the electrochemical performance of CA / (Fe / C-8)-10, electrochemical tests were performed in a two-electrode system. Figure 6 As shown, when the current density is 0.5A / g and the charge and discharge voltage is in the range of 0-2.1V, the discharge time of the dual electrode is 2800s, that is, when the power density is 526.89W / kg, the energy density is 409.8Wh / kg. Compared with the Fe / C-8 obtained in step 2, after compounding with CA, the discharge time can be significantly increased by 360%, and the energy density can be significantly increased by 362%.
[0100] In order to prove the cycling stability of CA / (Fe / C-8)-10, cycling tests were carried out in a dual-electrode system. Fig. 9As shown, under the condition of current density of 5 A / g, the number of cycles is 10,000 times and the capacity retention rate is 231%.
[0101] In order to demonstrate the influence of the calcination temperature in step 2.1, that is, the effect of the preparation process, comparative example 1 is provided, which is a zinc-containing porous carbon prepared at a calcination temperature of 600°C.
[0102] Comparative Example 1
[0103] A zinc-containing porous carbon prepared at a calcination temperature of 600°C, the steps not specifically described are the same as those in Example 1, except that: in the step 2.1, the calcination temperature is 600°C, and the material obtained in step 2.1 is zinc-containing porous carbon, referred to as ZnO / C.
[0104] In order to prove the composition of ZnO / C, XRD test was carried out. The test results are as follows Figure 1 As shown, ZnO / C has characteristic peaks of ZnO in addition to carbon. The test results show that at a lower calcination temperature, Zn element exists in the carbon material in the form of oxide.
[0105] By comparing the test results of ZnO / C and C-8 obtained in Example 1, it can be seen that the Zn element will be removed at a higher calcination temperature. The reason is that the boiling point of Zn is 907°C, so the calcination temperature must be greater than 907°C to achieve the technical effect of removing the Zn element.
[0106] It can be seen from Comparative Example 1 and Example 1 that after the calcination temperature reaches 950°C, the metal element Zn in C-8 volatilizes, and only the characteristic peak of carbon exists in the XRD test results, which proves the role of ZIF-8 in the technical solution.
[0107] In order to demonstrate the role of C-8 in the technical solution, Comparative Example 2 is provided, which is a composite material in which iron nanoparticles are directly loaded on the carbon aerogel.
[0108] Comparative Example 2
[0109] A composite material of carbon aerogel loaded with iron nanoparticles, wherein the steps not specifically described are the same as those of Example 1, except that: when performing step 2, step 2.1 is not required, and in step 2.2, porous carbon C-8 is not added to obtain iron nanoparticles, and then, in step 3, iron nanoparticles are used instead of iron nanocarbon balls to obtain a composite material CA / Fe in which iron nanoparticles are directly loaded on carbon aerogel. Specifically, the carbon aerogel loaded with iron nanoparticles obtained in Comparative Example 2 is named CA / Fe-10.
[0110] In order to verify the composition of the obtained CA / Fe-10, XRD test was performed. The test results are shown in Figure 5As shown, CA / Fe-10 has characteristic peaks of both carbon and Fe3O4. Compared with Example 1, it can be seen that the introduction of C-8 has no substantial effect on the composition of CA / Fe-10.
[0111] In order to prove the electrochemical performance of CA / Fe-10, GCD test was carried out. The test results are shown in Figure 4 As shown, when the current density is 0.5A / g, the voltage range of charge and discharge is -1-0.5V, and the discharge time is 390s. Compared with the test results of CA, it can be seen that after loading Fe3O4, the discharge time of CA / Fe-10 only increased by 59s, and the improvement was only 17.8%, which is far lower than the improvement effect of CA / (Fe / C-8)-10. The test results show that the introduction of C-8 to make Fe3O4 coated porous carbon can significantly improve the electrochemical performance. The reason is that Fe3O4 coated porous carbon can improve the overall conductivity, promote electron transfer, and improve electrochemical performance.
[0112] In order to demonstrate the effect of CA addition on performance, comparative example 3 is provided, in which a carbon aerogel and iron nano-carbon spheres are loaded with iron nano-carbon spheres in a mass ratio of 8:1.
[0113] Comparative Example 3
[0114] A method for preparing carbon aerogel-loaded iron nano-carbon spheres with a CA:Fe / C-8 ratio of 8:1, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 3, the mass ratio of CA to Fe / C-8 is 8:1, specifically, the amount of CA added is 0.25 g, and the amount of Fe / C-8 added is 0.03125 g. The carbon aerogel-loaded iron nano-carbon spheres obtained in the specific comparative example 3 are named CA / (Fe / C-8)-8.
[0115] In order to prove the composition of the obtained CA / (Fe / C-8)-8, XRD test was carried out. The test results are as follows Figure 5 As shown, CA / (Fe / C-8)-8 has characteristic peaks of both carbon and Fe3O4. Compared with Example 1, it can be seen that changing the mass ratio of CA to Fe / C-8 has no substantial effect on the composition of CA / (Fe / C-8)-8.
[0116] In order to prove the electrochemical performance of CA / (Fe / C-8)-8, GCD test was carried out. The test results are shown in Figure 4 As shown, when the current density is 0.5A / g, the voltage range of charge and discharge is -1-0.5V, and the discharge time is 486s. Comparing the test results with those of Example 1, it can be seen that reducing the amount of CA added directly leads to a reduction of 41s in the discharge time.
[0117] In order to further quantify the electrochemical performance of CA / (Fe / C-8)-8, electrochemical tests were performed in a two-electrode system. Figure 6 As shown in the figure, when the current density is 0.5A / g, the voltage range of charge and discharge is 0-2.1V, and the discharge time is 1620s; that is, when the power density is 525W / kg, the energy density is 236.25Wh / kg. The test results are compared with those of Example 1, and it can be seen that reducing the amount of CA added directly leads to a significant reduction in the discharge time, with a reduction of 73%. At the same time, the energy density is also significantly reduced, with a reduction of 73.4%.
[0118] By comparing Comparative Example 3 with Example 1, it can be seen that regulating the mass ratio of CA to Fe / C-8 can significantly affect the power density and energy density of the obtained material. The reason is that when there is less CA, that is, more Fe / C-8, an oversaturated load phenomenon will occur, which directly leads to the inability of Fe / C-8 to be effectively dispersed on CA, resulting in agglomeration, resulting in uneven distribution of Fe / C-8 on CA.
Claims
1. A carbon aerogel loaded with iron nanocarbon spheres, characterized in that: Chitosan and glacial acetic acid are used as raw materials, and carbon aerogel is obtained by freeze-drying and then calcining at high temperature; zinc nitrate hexahydrate, 2-methylimidazole, methanol and ethanol are used as raw materials, and porous carbon is obtained by standing at room temperature and then calcining at high temperature; iron nano-carbon balls are obtained by hydrothermal reaction of ferric chloride and porous carbon as raw materials; the carbon aerogel-loaded iron nano-carbon balls are composed of a lamellar structure and a nano-spherical structure, wherein the nano-spherical structure is loaded on the surface of the lamellar structure.
2. The carbon aerogel-loaded iron nano-carbon sphere according to claim 1, characterized in that: The specific surface area of the carbon aerogel is 950-1000m 2 / g, contains a large number of micropores and mesopores, and the specific surface area of the carbon aerogel loaded with iron nanocarbon spheres is 750-800m 2 / g, including micropores and mesopores.
3. A method for preparing carbon aerogel-loaded iron nanocarbon spheres, characterized in that The following steps are involved: Step 1, preparation of chitosan-based carbon aerogel, first, chitosan and glacial acetic acid meet a certain mass ratio, chitosan is dissolved in an aqueous solution to obtain a chitosan solution, then the chitosan solution is stirred under certain conditions, then glacial acetic acid is added to the chitosan solution, and stirring is continued under certain conditions, freeze-dried after stirring, and finally, the obtained product is calcined under certain conditions to achieve carbonization, so as to obtain chitosan-based carbon aerogel, referred to as CA; Step 2, preparation of Fe3O4-coated porous carbon nanospheres, first prepare a porous carbon material based on ZIF-8, and then coat Fe3O4 on the porous carbon material to obtain Fe3O4-coated porous carbon nanospheres, i.e., iron nanocarbon spheres, referred to as Fe / C-8; wherein, The preparation of the porous carbon material based on ZIF-8 is step 2.1, specifically, the preparation of porous carbon, first, 2-methylimidazole and zinc nitrate satisfy a certain mass ratio, 2-methylimidazole is dissolved in a mixed solvent to obtain an imidazole solution, and at the same time, zinc nitrate solid is dissolved in a mixed solvent to obtain a zinc nitrate solution, and then, at room temperature and under ultrasonic conditions, the imidazole solution is slowly poured into the zinc nitrate solution to obtain a mixed solution, and then, the mixed solution is stirred under certain conditions, and after stirring, ZIF-8 can be obtained by standing, centrifugal washing and vacuum drying, and finally, ZIF-8 is calcined under certain conditions to achieve carbonization, and the calcined product can be ground to obtain porous carbon, referred to as C-8; The preparation of Fe3O4-coated nanoporous carbon spheres is step 2.2, specifically, the preparation of Fe3O4-coated nanoporous carbon spheres, first, porous carbon, ferric chloride, anhydrous sodium citrate and anhydrous sodium acetate satisfy a certain mass ratio, the porous carbon, ferric chloride and anhydrous sodium citrate obtained in step 2.1 are placed in an ethylene glycol solution to obtain a solution A, then the solution A is stirred under certain conditions to obtain a solution B, then anhydrous sodium acetate is placed in the solution B to obtain a solution C, then the solution C is continued to be stirred under certain conditions to obtain a reaction solution, finally, the reaction solution is hydrothermally treated under certain conditions, the obtained product is washed and dried, and Fe3O4-coated nanoporous carbon spheres, i.e., iron nanocarbon spheres, referred to as Fe / C-8; Step 3, preparation of carbon aerogel-loaded iron nano-carbon spheres. First, with iron nano-carbon spheres, anhydrous sodium citrate and carbon aerogel satisfying a certain mass ratio, the iron nano-carbon spheres obtained in step 2.2, the carbon aerogel obtained in step 1 and anhydrous sodium citrate are placed in an ethylene glycol solution to obtain a D solution. Then, the D solution is stirred under certain conditions to obtain an E solution. Subsequently, the E solution is hydrothermally treated under certain conditions, and the obtained product is washed and dried to obtain carbon aerogel-loaded iron nano-carbon spheres, referred to as CA / (Fe / C-8).
4. The preparation method according to claim 3, characterized in that: In the step 1, the mass ratio of chitosan to glacial acetic acid is 5:3; In step 1, the freeze-drying conditions are at -50°C for 65-75h; In step 1, the calcination conditions are: the calcination temperature is 800° C. and the calcination time is 1-2 h.
5. The preparation method according to claim 3, characterized in that: In the step 2.1, the mass ratio of 2-methylimidazole to zinc nitrate is (1-2):1; the mixed solvent is a mixed solution of methanol and ethanol, and the volume ratio of methanol to ethanol is 1:1; In the step 2.1, the stirring conditions of the mixed solution are: the stirring speed is 500-1500 rpm, and the stirring time is 5-15 min; In step 2.1, the centrifugal washing conditions are: the centrifugal speed is 8000 rpm, the centrifugal time is 5 min, the washing solution is ethanol, and the number of centrifugal washings is 4-6 times; In step 2.1, the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 6-10 h. In step 2.1, the calcination conditions are: the calcination temperature is 950° C. and the calcination time is 1-2 h.
6. The preparation method according to claim 3, characterized in that: In the step 2.2, the mass ratio of porous carbon, ferric chloride, anhydrous sodium citrate and anhydrous sodium acetate is 1:10:(3-4):20; In step 2.2, the hydrothermal conditions are 200° C. for 15-17 h; In the step 2.2, the drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 10-14 h.
7. The preparation method according to claim 3, characterized in that: In the step 3, the mass ratio of iron nanocarbon spheres, anhydrous sodium citrate and carbon aerogel is 1:8:10; In step 3, the hydrothermal condition is 200° C. for 15-17 h; In step 3, the drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 10-14 hours.
8. The carbon aerogel-loaded iron nano-carbon sphere according to claim 1, characterized in that: When used as a supercapacitor electrode material, in three electrodes, when the current density is 0.5A / g, the charge and discharge voltage range is -1-0.5V, and the discharge time is 500-550s.
9. The carbon aerogel-loaded iron nano-carbon sphere according to claim 1, characterized in that: When used as a supercapacitor electrode material, in a double electrode, when the current density is 0.5A / g, the charge and discharge voltage range is 0-2.1V, and the discharge time is 2500-3000s, that is, under the condition of power density of 520-530W / kg, the energy density is 400-410Wh / kg.
10. The carbon aerogel loaded with iron nano-carbon spheres according to claim 1, characterized in that: When used as a supercapacitor electrode material, the capacity retention rate is 231% after 10,000 cycles at a current density of 5 A / g.
Citation Information
Patent Citations
Carbon aerogel / metal oxide composite material and preparation method and application thereof
CN107134373A
Fe3O4 coated porous carbon nanosphere as well as preparation method and application thereof
CN118942923A